Procesos de producción y su incidencia en la microempresa embutidora Funorsal de la corporación gruppo Salinas del cantón Guaranda provincia Bolívar, año 2024 - Tualombo Rochina, Isaías Daniel (2025)
The main objective of this work is to identify the key aspects of the production processes, to propose strategies and address the different deficiencies of the FUNORSAL filler, improve its processes and meet both individual and organizational objectives. Through a chi square analysis, it was shown that production processes have a significant impact on the FUNORSAL filler, which led to rejecting the null hypothesis. The investigation reveals that production processes significantly affect production in the filler, indicating the need to update and standardize the process manual to guide employees and reduce errors. The lack of a specific training guide for collaborators is also identified, which should cover key aspects of the production processes. These findings not only support future improvement strategies, but also highlight the importance of continuous training for the sustainable growth of the FUNORSAL filler. The results obtained show that, although the microenterprise has a structured production process, there are deficiencies in resource management and the implementation of quality controls that affect the consistency of the final product, which limits the adoption of more efficient practices. and sustainable. Based on these findings, recommendations are proposed to optimize production processes, improve product quality, and increase FUNORSAL's competitiveness in the local market